Faktor Human Capital Pada Pertumbuhan Ekonomi Kreatif - Nizar, Nefo Indra; Nazir, Ahmad (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2020)
The creative economy is a promising sector of economic growth and can become a new national economic power in the future. Contributions to the National GDP continue to increase from year to year. In 2016, the creative economy sector was able to contribute 7.44 percentages to the National GDP or a total of 922.59 trillion. One of the most important factors in the growth of the creative economy is human capital. Human capital is a stock of people in the form of education, skills and health so as to provide productivity which in turn will provide added value and economic value in the form of increased output and economic growth, including creative economic growth. The purpose of this study is to determine the role and influence of human capital on creative economic growth. The research method uses panel data on the basis of economic theory regarding human capital and economic growth theory. Secondary data sources were taken from BEKFRAF and BPS for GRDP data of five provinces during the period of 2011-2016. Human capital indicators used in this study are the number of people working in the creative economy sector and the Human Development Index (HDI). HDI represents the three basic human dimensions, namely the dimension of longevity and health, the dimension of knowledge, and the standard dimension of living standards. Economic growth using GRDP data. From the estimation results of research that human capital factors contribute positively to the growth of the creative economy. Abstrak Ekonomi kreatif merupakan sektor yang menjanjikan terhadap pertumbuhan ekonomi dan dapat menjadi kekuatan baru ekonomi nasional di masa yang akan datang. Kontribusi terhadap PDB Nasional terus meningkat dari tahun ke tahun. Pada tahun 2016, sektor ekonomi kreatif mampu meyumbang 7,44 persen terhadap PDB Nasional atau total sebesar 922,59 triliun. Salah satu faktor yang paling penting di dalam pertumbuhan ekonomi kreatif adalah human capital. Human capital merupakan stock dari manusia yang berupa pendidikan, ketrampilan dan kesehatan sehingga dapat memberikan produktivitas yang pada gilirannya akan memberikan nilai tambah dan nilai ekonomi berupa peningkatan output dan pertumbuhan ekonomi, termasuk pertumbuhan ekonomi kreatif. Tujuan dari penelitian ini adalah untuk mengetahui peran dan pengaruh human capital terhadap pertumbuhan ekonomi kreatif. Metode penelitian menggunakan data panel dengan basis teori ekonomi mengenai human capital dan teori pertumbuhan ekonomi. Sumber data sekunder diambil dari BEKFRAF dan BPS untuk data PDRB lima provinsi selama rentang waktu 2011 – 2016. Indikator human capital yang digunakan dalam penelitian ini adalah jumlah penduduk yang bekerja di sektor ekonomi kreatif dan Indeks Pembangunan Manusia (IPM). IPM mewakili tiga dimensi dasar manusia, yaitu dimensi umur panjang dan sehat, dimensi pengetahuan, dan dimensi standar layak hidup. Pertumbuhan ekonomi menggunakan data PDRB. Dari hasil estimasi penelitian bahwa faktor human capital memberikan kontribusi positif terhadap pertumbuhan ekonomi kreatif. Kata Kunci : Human capital, Pertumbuhan Ekonomi Kreatif, Data Panel